A voltage unbalance factor coding technique for three‐phase induction motors. (30th January 2018) - Abu‐Elhaija, Wejdan; Muetze, Annette
Summary: This work investigates the effect of voltage unbalance on the starting and steady‐state performances of squirrel cage induction motors. Emphasis is placed on the rotor flux and slip. Both copper losses accumulated during the run up and at steady state are investigated. Five motor ratings of up to 4000 kVA operating at partial and at full load are studied. Because the same voltage unbalance factor may result in different behaviors, a voltage code is proposed to simplify referring to the individual per unit phase magnitudes. Full load operation at a voltage unbalance factor higher than 3.5% showed an increase of copper losses of more than 50%. Voltage unbalance cases that fail to pull up the motor to at least 50% of the rated speed show rotor fluxes too low to generate the required torque.